Open-circuit fault detection of inverter fed PMSM for electrical powertrain applications - Haidar, Fatima; Douiri, Takwa Sellami; Bartoli, Thomas (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper aims to enhance the reliability of power electronic converters fed permanent magnet synchronous machine for electrical powertrain applications. Many faults like open circuit may affect the power converter and quickly lead to a decline in supplied power quality and all the power train components behavior. In this framework, this paper proposes an open circuit fault detection scheme for inverters. First, the dynamic models of the powertrain subsystems were developed. In fact, all the mathematics models of the motor, inverter, power converter, battery and charger are presented. Then, a detection scheme of open-circuit fault in inverter/motor. The control schemes were elaborated based on current analysis method. The diagnosis strategy under discontinuous switch-ing dynamics of the DC/AC inverter is proposed.